Participation, social capital and empowerment among members of Kankara Local Community Fadama user groups in Katsina State, Nigeria - Rilwanu, Aminu (2014)
The main purpose of this study is to explain the participatory process of Kankara local community Fadama members with regards on social capital and empowerment. Fadama activity is a project initiated by local community, supported by Nigerian Government and some Non-Governmental Organization (NGOs) for the purpose of empowering the members of Fadama User Groups (FUGs). The project focuses particularly on poverty eradication and improvement of the quality life of the rural people. The research objectives are: to describe the level of participation, social capital and empowerment, to identify the differences in participation, social capital and empowerment based on age, gender, level of education and level of income; to determine the relationship of participation, social capital and empowerment, and to determine the unique predictors to empowerment. Finally, the research has determined the mediating effects of social capital on the relationship between participation and empowerment. A total of 285 respondents were randomly selected in this study. They were Fadama User Groups (FUGs) of Kankara local community, Katsina state, Nigeria. The study was designed quantitatively by using questionnaire as a tool in data collection process. The researcher administered the questionnaire himself and assisted by some trained enumerators. The researcher used descriptive statistics, t-test, ANOVA, correlation and regression analysis. Finally Sobel mediation test was also employed. The result shows that there were no significant difference in participation, social capital and empowerment based on age, gender, level of education and level of income. Pearson correlation indicated that there were significant moderate relationships between participation, social capital and empowerment. The two variables, participation and social capital transgressed to empowerment (R2 = .207, and adjusted R2 = .201. While the Sobel mediation test shows that participation has significant effect on empowerment through social capital (z = 4.115, p = 0.000). The study recommended that, the subsequent study may emphasize on young age group of 20-35years, among the women user groups (WUGs).